The Aeneid - Virgil; Ruden, Sarah (New Haven : Yale University Press, 2008)
A retelling of Virgil's Aeneid.
Translator's Preface -- Book 1 -- Book 2 -- Book 3 -- Book 4 -- Book 5 -- Book 6 -- Book 7 -- Book 8 -- Book 9 -- Book 10 -- Book 11 -- Book 12 -- Glossary.
Translated from the Latin.
Print version record.
eBooks on EBSCOhost
Keywords: Aeneas -- (Legendary character) -- Poetry; Aeneas -- (Legendary character); Vergilius Maro, Publius -- v70-v19; Epic poetry, Latin -- Translations into English; Legends -- Rome -- Poetry; Légendes -- Rome -- Poésie.; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Epic poetry, Latin; Legends; Rome (Empire); Lateinunterricht; epic literature; epic poems; legends (literary genre); Epic poetry; Legends; Epic poetry, Latin; Poetry; Translations; Epic poetry; Legends; Epic poetry; Légendes.; Poésie épique.